SEMANTIC CAUSATIVES USAGE IN FINDING NEMO 2003 MOVIE - Sa'pang, Rosalina; Aso, La; Masri, Fina Amalia (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2023)
The objective of this study is to describe how semantic causatives are used in Finding Nemo movie based on Shibatani’s theory. Semantic causative expresses a causal relationship between two occurrences or actions. This study used a qualitative descriptive type where the source of data in this study was Finding Nemo movie, while the data itself were the written utterances. The data were collected by searching and downloading the movie, transcribing the utterances of the dialog, and identifying the data. The data were analyzed by presenting, describing, interpreting and concluding the data. semantic causatives include state and action, transitivity, control, volition, affectedness, directness, intention, naturalness, and involvement. The result show, that the use of semantic causatives in Finding Nemo movie involve the causer and causee parameters, that is, directness, intention, naturalness, involvement, control, volition, affectedness, and also the verb parameters of state/action and transitivity. These parameters indicate the relationship between the cause and effect and causality in this movie. Semantic causative plays a significant role in shaping the narrative and character actions. Semantic causative is the relationship between cause and effect, and it is a fundamental storytelling element that helps drive the plot forward and create emotional engagement with the audience.